Management of downy mildew of blond psyllium through seed treatment-cum-foliar sprays - V.N. PATHAK, B.S. RATHORE and (Indian Phytopathology, 2002)
Efficacy of different fungicides as seed treatment or foliar sprays were tested against downy mildew of 'Isabgol' or blond psyllium (Plantago ovalo Forsk) caused by Peronospora alto Fuckel under artificial epiphytotic conditions. In a two year field study, seed treatment with Apron 35 SO (5 g/kg seed) followed by three sprays of Ridomil MZ 72 WP (0.2%) were found effective in reducing systemic as well as non-systemic infection of downy mildew and in increasing the seed yield.